Send to me first: Priority in synchronous message-passing. (22nd December 2022) - CHUANG, CHENG-EN; IRACI, GRANT; ZIAREK, LUKASZ
Abstract: In this paper, we introduce a tiered-priority scheme for a synchronous message-passing language with support for selective communication and first-class communication protocols. Crucially, our scheme allows higher priority threads to communicate with lower priority threads, providing the ability to express programs that would be rejected by classic priority mechanisms that disallow any (potentially) blocking interactions between threads of differing priorities. We formalize our scheme in a novel semantic framework featuring a collection of actions to represent possible communications. Utilizing our formalism, we prove several important and desirable properties of our priority scheme. We also provide a prototype implementation of our tiered-priority scheme capable of expressing Concurrent ML and built in the MLton SML compiler and runtime. We evaluate the viability of our implementation through three case studies: a prioritized buyer-seller protocol and predictable shutdown mechanisms in the Swerve web server and eXene windowing toolkit. Our experiments show that priority can be easily added to existing CML programs without degrading performance. Our system exhibits negligible overheads on more modest workloads.